Reducing Body Dysmorphic Disorder Tendencies by Thinking Positively in Early Adulthood - Nurfina, Nana; Rahmat Hidayat, Dede (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction:  dissatisfaction with body shape is a phenomenon that is often encountered today, excessive dissatisfaction with body shape parts can cause a tendency to mental disorders called body dysmorphic disorder. Individuals with a tendency to body dysmorphic disorder tend to improve their appearance, go on strict diets, and exercise excessively, which activities can endanger the health of the individual. Objective: to determine the relationship between positive thinking and the level of tendency to body dysmorphic disorder in early adulthood in Bekasi City Method: This study uses a quantitative approach with a correlational method. Result and Discussion: Data in this study  were analyzed using non-parametric spearman test technique, with results obtained of -0.429** and significance results of <0.001 (p<0.01), Conclusions: this study shows that individuals who think positively can change negative body image into positive because of the ability to think positively so as to reduce the level of tendency to body dysmorphic disorder in adult individuals beginning